Amino acid analysis in wines by liquid chromatography : UV and fluorescence detection without sample enrichment - Douglas, C. A. (Claire Anne) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2003.